2021
DOI: 10.1007/s40124-021-00257-6
|View full text |Cite
|
Sign up to set email alerts
|

Current Insights Into the Pathophysiology of Multisystem Inflammatory Syndrome in Children

Abstract: Purpose of Review We highlight the new clinical entity multisystem inflammatory syndrome in children (MIS-C), the progress in understanding its immunopathogenesis, and compare and contrast the clinical and immunologic features of MIS-C with Kawasaki disease (KD). Recent Findings Studies show immune dysregulation in MIS-C including T lymphocyte depletion and activation, T cell receptor Vbeta skewing, elevated plasmablast frequencies, increased markers of vascular patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 70 publications
3
77
0
Order By: Relevance
“…In our pediatric cohort, only one Hispanic patient developed a transient ectasia of the main left coronary, which quickly resolved after therapy. There are conflicting descriptions about the data regarding the involvement of coronary arteries; the incidence of coronary artery dilatation/aneurysms varies significantly among reports (8-24%) [14,29], and the pathological mechanism is, as yet, unknown. Abrams et al showed some degree of association between muco-cutaneous alterations, conjunctival hyperemia, and coronary artery alterations, suggesting a possible overlap between MIS-C and Kawasaki disease [22].…”
Section: Discussionmentioning
confidence: 99%
“…In our pediatric cohort, only one Hispanic patient developed a transient ectasia of the main left coronary, which quickly resolved after therapy. There are conflicting descriptions about the data regarding the involvement of coronary arteries; the incidence of coronary artery dilatation/aneurysms varies significantly among reports (8-24%) [14,29], and the pathological mechanism is, as yet, unknown. Abrams et al showed some degree of association between muco-cutaneous alterations, conjunctival hyperemia, and coronary artery alterations, suggesting a possible overlap between MIS-C and Kawasaki disease [22].…”
Section: Discussionmentioning
confidence: 99%
“…MIS-C is better characterized than long COVID. It is an acute and potentially fatal condition that occurs after 2 to 6 weeks after SARS-CoV-2 infection in less than 0.1% of pediatric COVID-19 cases and that is associated with marked immune activation and many potential mechanisms of immunopathogenesis [5]. Children with MIS-C present with several multisystemic manifestations, among which those involving the gastrointestinal tract, the skin and the mucous membranes, and the cardiovascular system are the most common.…”
Section: Introductionmentioning
confidence: 99%
“…If true, this should be considered in vaccine development against SARS-CoV-2 [ 100 ]. Further studies implied the pathogenesis consistent with the postinfectious inflammatory syndrome, characterised by an elevation in all cytokines and markers of recent T-cell activation (sIL-2R) despite a strong and specific humoral response to SARS-CoV-2 [ 102 , 113 ].…”
Section: Multisystem Inflammatory Syndrome In Children (Mis-c)mentioning
confidence: 99%